Bell-state tomography in a silicon many-electron artificial molecule - Ross C. C. Leon (Nature Portfolio, 2021)
Multielectron quantum dots offer a promising platform for high-performance spin qubits; however, previous demonstrations have been limited to single-qubit operation. Here, the authors report a universal gate set and two-qubit Bell state tomography in a high-occupancy double quantum dot in silicon.